Sexuality Education at University Level - Accounting for the Experience of the Seminar held in 2018 at the Faculty of Humanities and Sciences of Universidad Nacional del Litoral (Itinerarios Educativos, 2019)
This article is intended to give an accounton the Optional Seminar ‘Gender and ComprehensiveSexuality Education in an Interpellation to Sciencesand Public Policies’ held in 2018 at the Faculty ofSciences and Humanities, Universidad Nacional delLitoral (FHUC-UNL, for their Spanish initials). Thispaper shows some lines about the context of theemergence of proposals, pedagogical decisions, didacticdilemmas, and some temporary certainties fromthe viewpoint of the faculty and retrieving the views ofthe participating students. Teaching and learning areprivileged human practices to rethink about oneself/ourselves/others in terms of sexual rights, disclosingthe matrices which perpetuate homo-lesbo-transphobicsexism as regards bodies, pleasure, and desire,revisiting disciplinary areas, education, and professionalpractices. The proposal is contextualized ina feminist pedagogical approach that calls for horizontality,collective work, and participation with thefreedom required to discuss the addressed issues andeven to express different positions. Reflecting on thedelivery of this seminar aims at demonstrating that comprehensivesexuality education at university level opensthe ways to imagine strategies for building gender and sexjustice from professional performance, which is not onlydesirable but, above all, possible.
Keywords: Comprehensive Sexuality Education · gender · university · feminist pedagogy